Assessing the use of the IUGA/ICS classification system for prosthesis/graft complications in publications from 2011 to 2015. Issue 12 (December 2016) - English, Emily; Solomon, Megan; Chen, Bertha; Rogo-Gupta, Lisa
Abstract Introduction and hypothesis Complications of pelvic organ prolapse and urinary incontinence surgery have gained increasing attention from both lay media and medical societies. The International Urogynecological Association and International Continence Society proposed the category–time–site system to classify complications in 2011. Our objective is to assess the usage of the category–time–site system in the literature. Methods We conducted a systematic review and identified records using PubMed search terms "mesh" and "prolapse or incontinence" and "complication or excision" (February 2011 to December 2015) to select publications following the introduction of category–time–site system. Relevant publications were included and reviewed for study design, initial procedure, number of patients assigned codes, number of unique codes applied, purpose of assigning codes, and duration of clinical follow-up. Results Of 167 eligible records, 23 (14 %) used the system, 137 (82 %) used no system, and 7 (4 %) used another system. They included three study designs: randomized control trials, case reports, and case series. Given the very limited amount of data, no statistical tests were performed, but trends were noted. Conclusions Fourteen percent of the reports in the literature describing complications related to prosthesis/graft use in pelvic surgery utilize the category–time–site system. The system's limited and inconsistent use hinders the ability to draw conclusions useful for clinical practice. Effort should be directed toward improving appropriate usage or revising the system to increase its exposure in related publications. An improved system will better prepare pelvic surgeons for assessing future generations of prostheses/grafts.